S17 A prothrombotic state is associated with increased mortality in idiopathic pulmonary fibrosis. (14th November 2013) - Navaratnam, V; Fogarty, A; McKeever, T; Thompson, N; Jenkins, RG; Johnson, SR; Dolan, G; Kumaran, M; Pointon, K; Hubbard, RB
Abstract : Background: Our previous case-control study demonstrated that a prothrombotic state was almost five times more common in people with idiopathic pulmonary fibrosis (IPF) than general population controls. We followed up the incident cases of IPF to determine if a prothrombotic state altered prognosis in terms of survival. Methods: People with IPF were recruited from five teaching and eight district general hospitals in England and Wales. All participants were asked for details of medical history, medication and smoking habit. Venous blood samples were taken to test for inherited and acquired clotting defects. We also collected high resolution computed tomography (HRCT) scans and pulmonary function tests done as part of routine care. All HRCT scans were reviewed by two thoracic radiologists to confirm the diagnosis of IPF. A prothrombotic state was defined as having at least one of the inherited or acquired clotting defects tested. Cox regression modelling was used to investigate the association between a prothrombotic state and survival amongst people with IPF, adjusting for age, sex, highly sensitive C Reactive Protein (hsCRP), smoking habit and baseline pulmonary function indices. Results: There were 211 incident cases of definite or probable IPF with a median follow up of 2 years (IQR: 1.2 to 2.5). During this time, 86 out of the 211 (40.8%) cases died, which equates to an overall mortality rate of 220.5 per 1000 person years (95% CI: 178.2 to 272.7). 78 out of the 86 deaths (90.7%) were in individuals with a prothrombotic state (see Table 1 ). The proportion of the IPF cohort surviving at 2 years was 84.7% in patients without any clotting defects and 61.1% in patients with a prothrombotic state (p = 0.0035). Conclusions: A prothrombotic state is associated with increased mortality amongst people with IPF. Further research into manipulation of the clotting cascade to improve the outlook of people with IPF is warranted.